2022
DOI: 10.24272/j.issn.2095-8137.2021.266
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome resequencing infers genomic basis of giant phenotype in Siamese fighting fish (<i>Betta splendens</i>)

Abstract: A: Giant and normal bettas. B: LD decay among wild-type, giant, and normal bettas. C, D: Population structure within betta fish and between giant and normal bettas, respectively, as revealed by PCA. E: Ancestral genetic clusters among wild-type, giant, and normal bettas, as revealed by admixture analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Over past 100 years, more than 1000 scientific papers on fighting fish have been published by scientists from many countries 4,5,12,13,18,20,62,70 . Since 2018, publications have numbered over 100 per year and continued to increase yearly.…”
Section: New Insights Into Phenotypes Sex Determination Domestication...mentioning
confidence: 99%
See 4 more Smart Citations
“…Over past 100 years, more than 1000 scientific papers on fighting fish have been published by scientists from many countries 4,5,12,13,18,20,62,70 . Since 2018, publications have numbered over 100 per year and continued to increase yearly.…”
Section: New Insights Into Phenotypes Sex Determination Domestication...mentioning
confidence: 99%
“…A recent GWAS showed that body size was determined by many QTL scattered across different regions of the fighting fish genome. Many candidate genes for growth were identified, 18,20 however, the functions of these genes have not been investigated. Further study using genomics tools, 3,12,13,18,20,76 including knockout with CRISPR/Cas9, 69 may bring novel insights into how these genes determine body size.…”
Section: New Insights Into Phenotypes Sex Determination Domestication...mentioning
confidence: 99%
See 3 more Smart Citations